2021
DOI: 10.30595/alphamath.v7i1.10199
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Creativity In Mathematic Using SAVI (Somatic Auditory Visual Intellectual) Approach

Abstract: The low level of student creativity is a reflection of the unsuccessful learning process. Thus, it needs a special treatment to solve it. The study aims to increase student creativity using the SAVI method for 4th semester students of the Mathematic Education Study Program. This research is a classroom action research. Research with a focus on increasing student creativity using the SAVI method was conducted in semester 4 of the Mathematic Education Study Program, with 44 students. This research was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Untuk mendukung proses pembelajaran yang mampu meningkatkan aktivitas belajar peserta didik secara menyeluruh dan melibatkan seluruh inderanya bekerja, dibutuhkan model pembelajaran yang sesuai. Konteks ini sesuai dengan salah satu model pembelajaran yakni SAVI (Somatic, Auditory, Visual, dan Intellectual), yang memadukan aktivitas fisik dan intelektual dengan menggunakan seluruh indera dan tubuh serta pikiran dalam proses pembelajaran [10].…”
Section: Pendahuluanunclassified
“…Untuk mendukung proses pembelajaran yang mampu meningkatkan aktivitas belajar peserta didik secara menyeluruh dan melibatkan seluruh inderanya bekerja, dibutuhkan model pembelajaran yang sesuai. Konteks ini sesuai dengan salah satu model pembelajaran yakni SAVI (Somatic, Auditory, Visual, dan Intellectual), yang memadukan aktivitas fisik dan intelektual dengan menggunakan seluruh indera dan tubuh serta pikiran dalam proses pembelajaran [10].…”
Section: Pendahuluanunclassified
“…Ahmad and Mohamed revealed that SAVI is learning by combining physical and intellectual activities and involving all the senses to progress learning 15 . Several studies that have been conducted show that the SAVI learning model influences increasing students' interest in learning.…”
Section: Introductionmentioning
confidence: 99%